Distorted social representations of science: A study with science teachers in initial training (Revista Contexto & Educação, 2026)
This study investigates the structure of social representations of science developed by pre-service science teachers and analyzes the conceptions they express. The research is based on the Theory of Social Representations, especially the structural approach. Forty-seven undergraduate students from a Biological Sciences course at a public university in Paraná participated, through the application of an online questionnaire made available on the Google Forms platform. The data analysis was performed based on the frequency and percentage of responses, in addition to using the EVOC software to process the ALP question. The results point to predominantly positive, neutral, and idealized representations of science, with little recognition of its limitations, controversies, and negative aspects. These findings reinforce the relevance of including curricular components focused on Epistemology, History, and Philosophy of Science in teacher training courses, in order to foster the construction of a broader, more critical, and contextualized understanding of scientific knowledge.
Keywords: Teacher Training; Science; Bachelor's Degree in Biological Sciences